New Economy: Evolution of Forms and Research Methodology - Kotlyarevskyy, Ya.V.; Melnychenko, A.A.; Ivanytska, O.M.; Semenyuk, E.P.; Kniaziev, S.I.; Melnikov, O.V. (Science and Innovation, 2024)
Introduction. The era of the scientific and technological revolution has qualitatively changed the content and balance of the processes of integration and differentiation of science, contributed to the development of interdisciplinary discourse in the field of scholarly research knowledge, in particular, the identification of the forms and research methodology inherent in the modern stage of the economic research evolution. Problem Statement. Amongst the synthetic integrative tendencies of economic research development, active impulses of scientific heuristics have been noticeably influenced, thus forming perspectives and guidelines for the evolution of cognition forms and methods. One such phenomenon is the formation of the new economy paradigm (from the economy of the information sphere to the digital economy) as a special kind of theoretical and applied research. In recent years, the active processes of conceptualization of the phenomenon of neo-economics and its structural elements have been observed in the scholarly research environment. Purpose. To generalize, to structure, and to systematize the development processes concerning the phenomenon of the traditional economy creativization as an integral factor (stimulator) of special forms (virtualization and typology) and methods (digitization and financialization) in the field of socio-economic relations cognition. Materials and Methods. The methodological framework of this study consists of a retrospective analysis of the context and directions of the information approach application in the process of integration, internal and transdisciplinary synthesis. Results. The new information and economic reality has been comprehended, and the principles of systematic research have been updated, which will contribute to solving the principal issues of the formation and implementation of effective economic, R&D and innovation policies. The creative economy and the development of the economy of the information sphere have been considered beyond the traditional boundaries of the cultural and digital industries. A complex vision of the consequences of their mutual intersection and exchange of solutions and tools in different spheres of social practice, which contributes to the development of a categorical-conceptual apparatus and methodological principles for scholarly research with consideration of social-economic relations in the modern society has been offered. Conclusions. In order to stimulate the development of a new economy, it is necessary to identify the factors contributing to the evolution of forms and methods of scholarly research knowledge and the transformation of traditional socio-economic relations into resources of a new formation.